Gain enhancement of slot array for base station using cavity of curved-woodpile metamaterial - Rangsan Wongsan (2018)
© 2016 IEICE. This paper proposes the gain enhancement of base station antenna for mobile phone by using the metamaterial structure associated with conventional slot array antenna. The new technique of cavity of curved-woodpile metamaterial on Electromagnetic Band Gap (EBG) structure has been utilized to improve the gain instead of increasing the number of slots on such an array. The proposed technique has the advantages of reducing the total length of slot array antenna but providing the higher gain. Furthermore, it provides the azimuth pattern covering 360 by using a triangular array configuration consisting of three panels of 1×4 slots array on each side of the triangle with the triangular PEC reflector for decreasing their back and side lobes. This idea has been verified by both the CST simulation software and experimental results. As the results, the prototype antenna achieves a high gain of 16.6 dB at 2.1 GHz.